Utilization of Geogebra Application as Learning Media in Learning The Three-Dimensional to Increase Students' Interest in Learning - Widyastiti, Maya; Yanti, Yusma; Sumarsa, Amar; Durrotul Faizah, Layla (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
This activity aims to describe students' interest in learning, learning outcomes, and the benefits of using GeoGebra in learning the three-dimensional. The data collected were analyzed using descriptive analysis. The research subjects were 59 students of SMA Negeri 1 Megamendung. Data collection techniques used tests and questionnaires. This research consists of 2 cycles. In cycle 1, the results obtained based on students' interest in learning showed that on average students strongly agreed 18.6%, agreed 31.1%, moderately 44.3%, and disagreed 5.9%. In cycle 2 after using the GeoGebra application, student interest increased to strongly agree 30.9%, agree 48.7%, moderately 18.6% and disagree 1.7%. Based on the learning outcomes in cycle 1, it shows 42.37% of students can solve problems well, while in cycle 2 there is an increase in the percentage of learning outcomes to 56.59%. Based on the results of the above analysis, it can be concluded that GeoGebra is very useful as a learning media and there is an increase in student interest and learning outcomes in learning the three-dimensional using GeoGebra.